Evaluasi dan Penilaian pada Pembelajaran Matematika - Magdalena Susanti Telaumbanua; Doni Berkat Tabah Hulu; Nesti Surya Astuti Zebua; Alianus Zalukhu; Herman Herman; Tutiarny Naibaho; Ruth Mayasari Simanjuntak (Journal on Education, 2023)
This study aims to evaluate and analyze various evaluation and assessment methods used in learning mathematics and their impact on student achievement. This study uses a qualitative approach by collecting data through classroom observations, interviews with mathematics teachers, and analysis of related documents. The results of this study indicate that there are various evaluation and assessment methods used in learning mathematics, including written tests, projects, presentations, and group assignments. Each method has different advantages and disadvantages, and provides various information about students' understanding and mathematical skills. In this regard, this study also highlights the importance of using a variety of evaluation and assessment methods that are sufficient to measure various aspects of learning mathematics, such as conceptual understanding, application in real-life contexts, problem solving, and critical thinking. This study also identified several challenges faced in the evaluation and assessment of learning mathematics, including difficulties in designing objective tests, measuring complex aspects of skills, and providing constructive feedback to students. Based on the results of this study, it is suggested that mathematics teachers continue to develop skills in designing and implementing evaluation and assessment methods that suit students' needs. In addition, training and professional support are needed to increase teachers' understanding of the principles of effective assessment in the context of learning mathematics. Collaborative efforts between teachers, students and other related parties also need to be increased to improve the quality of evaluation and assessment in learning mathematics.